2018
DOI: 10.1111/ejn.13801
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenomics – towards a more rigorous science

Abstract: OverviewThe field of neurogenomics is coming of age, but not without some teething problems. The aim of this field is to understand the genetic basis of differences in brain structure and function, which in turn underlie differences in behaviour, cognition, perception, mood and other psychological faculties, as well as susceptibility to psychiatric disorders. Both imaging and genomic technologies are now being applied on a very large scale, greatly boosting the potential power of this combined approach. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…First of all, the sample size was determined by study constraints and had a prevalence of the female gender. In the last decade, genetic association studies with limited sample sizes have become the target of increasing concerns related to the small variance explained in variables by one single-nucleotide polymorphisms (i.e., OXTr rs53576) [ 113 , 114 ]. However, given the difficulty of unraveling the nature of a given psychological construct (i.e., online social behavior) in a gene-environment perspective, the same experts of the fields cannot provide a definitive and unique solution to this implicit limitation [ 113 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…First of all, the sample size was determined by study constraints and had a prevalence of the female gender. In the last decade, genetic association studies with limited sample sizes have become the target of increasing concerns related to the small variance explained in variables by one single-nucleotide polymorphisms (i.e., OXTr rs53576) [ 113 , 114 ]. However, given the difficulty of unraveling the nature of a given psychological construct (i.e., online social behavior) in a gene-environment perspective, the same experts of the fields cannot provide a definitive and unique solution to this implicit limitation [ 113 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The genetic correlations approach one, indicating an almost complete shared genetic basis between meta‐analysis and one‐site analysis . A lack of strict statistical thresholds or requirements for replication have led to many publications without reproducible associations . We make the assertion that brain‐imaging traits are not special; hence, genetic associations to brain‐imaging traits are subject to the same statistical thresholds and replication criteria as all other traits.…”
Section: Genetic Associations To Neuroimaging Traitsmentioning
confidence: 87%
“…74 A lack of strict statistical thresholds or requirements for replication have led to many publications without reproducible associations. [75][76][77] We make the assertion that brainimaging traits are not special; hence, genetic associations to brain-imaging traits are subject to the same statistical thresholds and replication criteria as all other traits. With this in mind, here we focus on imaging genetic findings from large sample sizes reported by consortia.…”
Section: Genetic Associations To Neuroimaging Traitsmentioning
confidence: 99%
“…In particular, it has been shown that, in the context of GWASs, candidate genes for schizophrenia do not show stronger signals than non‐candidates (Johnson et al., ). Nonetheless, important challenges remain in neurogenomics more generally, not only in the study of language, as highlighted by Mitchell ().…”
Section: Functional Genetics and Neuronal Migrationmentioning
confidence: 99%